1997
DOI: 10.1002/(sici)1097-0215(19970611)71:6<917::aid-ijc1>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Oesophageal cancer in France: Potential importance of hot alcoholic drinks

Abstract: In France, major geographic variation exists in the incidence of oesophageal cancer, the highest incidence being reported in Normandy and Brittany. The role of alcohol in the risk of oesophageal cancer is well established in Western countries. One possible explanation for geographical variation of incidence is that higher incidence of oesophageal cancer is due to specific local alcoholic beverages. The aim of this study was to determine whether different types of alcoholic beverages exert different effects on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(25 citation statements)
references
References 17 publications
2
23
0
Order By: Relevance
“…This observation is particularly interesting, as previous epidemiological studies reported an association between oesophageal cancer and intake of hot mate (herbal tea) in South America, 45 46 and hot calvados in France. 47 However, the relatively limited numbers of patients in this study precluded further statistical analysis between patterns of p53 mutations and intake of hot beverages. Further confirmatory studies should also consider not only the temperature, but also the nature and chemical content of beverages.…”
Section: Discussionmentioning
confidence: 96%
“…This observation is particularly interesting, as previous epidemiological studies reported an association between oesophageal cancer and intake of hot mate (herbal tea) in South America, 45 46 and hot calvados in France. 47 However, the relatively limited numbers of patients in this study precluded further statistical analysis between patterns of p53 mutations and intake of hot beverages. Further confirmatory studies should also consider not only the temperature, but also the nature and chemical content of beverages.…”
Section: Discussionmentioning
confidence: 96%
“…METHODS A detailed description of the design and methods of the case-control study is available elsewhere. [6][7][8][9][10][11][12][13][14][15][16][17] Briefly, the study was carried out in the eastern part of Golestan province, northern Iran. Case participants were recruited between December 2003 and March 2007 at Atrak Clinic, the only gastrointestinal specialty clinic in the study area.…”
Section: Introductionmentioning
confidence: 99%
“…Some evidence of a protective effect of olive oil [45] has been observed, as well as a positive association with butter consumption [45,49]. Furthermore, diet implies exposure to other carcinogens ingested with foods and drinking water, such as N -nitroso compounds [47,50,51] or diarrhetic shellfish-poisoning toxins [52].…”
Section: Discussionmentioning
confidence: 99%